Characterization of Cassava Starch–Based Edible Film (Manihot esculenta) and Seaweed Na-Alginate with Variations in Drying Time - Trustha Aurora Firdauza; Widia Kristiana Putri; Harimbi Setyawati; Dwi Ana Anggorowati (Universitas Islam Raden Rahmat, Malang, 2026)
Edible films are biodegradable and consumable packaging materials that protect food products from environmental influences. This study aimed to produce and characterize cassava starch–based edible films with sodium alginate from seaweed, glycerol as a plasticizer, and garlic extract as an antibacterial agent using the solvent casting method. The research variables included cassava starch mass (4, 5, and 6 g) and drying time (4, 9, 14, 19, and 24 hours). Film thickness, tensile strength, elongation, moisture content, solubility, and microbiological properties were analyzed. Results showed that starch mass and drying time significantly affected the physical and mechanical properties of the films. The optimum drying time was 14 hours, at which all samples met the Indonesian National Standard (SNI) for moisture content (10–<16%). The best performance was obtained with 6 g starch, producing films with a tensile strength of 5.034 MPa, elongation of 13.48%, and low microbial counts (4–9 cells/100 mL) with negative Escherichia coli, complying with SNI 2897:2008. The addition of garlic extract contributed to the films’ antimicrobial properties. Overall, the formulation demonstrates a balanced combination of mechanical, physical, and microbiological characteristics, providing a practical foundation for developing biodegradable cassava starch–based edible films for food packaging applications.